DisCard – Mobile Application for Digitized Contactless Smart Cards Using Near Field Communication - Ghaisan Latheef, Mohamed; Ghaisan Latheef, Mohamed; A/P Ramachandiran, Chandra Reka (International Journal of Psychosocial Rehabilitation, 2019)
This paper proposes an online account for storing digitized copies of physical smart cards on the cloud, that are otherwise used for access credentials, subscription to various services, or loyalty programs. Instead of needing to carry around multiple cards for different purposes, or installing multiple separate applications, they can all be accessed by logging into the DisCard application on your chosen mobile device, which will use NearField Communication technology in order to emulate the physical card when swiped and scanned. How this application will work is explained, and why the author believes it is better than the currently implemented solution, being physically carrying multiple separate plastic cards with embedded chips. Afterwards, a few papers on related topics are reviewed, with said relation to the application presented, discussed. Results of exploratory surveys indicating viability in the consumer market is analysed and discussed. Positive impacts of switching to digital cards rather than physical ones are then brought to light, such as reduction of plastic waste being beneficial to the environment. Future ideas on improvements as well as limitations of the current application proposed are shown